Effect of Subsurface Drainage Spacing and Depth on Crop Yield. (1st July 2019) - Acharya, Umesh; Chatterjee, Amitava; Daigh, Aaron Lee M.
Abstract : Core Ideas: Subsurface drainage spacing affected corn and soybean production. Narrower subsurface drainage spacing removes excess water from the soil profile in the wettest year. Subsurface drainage depth does not affect corn and soybean production in a Fargo clay soil. Drainage design recommendations for the poorly‐drained, frigid clay soils continue to evolve in the Red River Valley of the North (RRVN). The objective of this 3‐yr (2015–2017) study was to evaluate subsurface drainage spacing (9, 12, and 15 m) and depth (0.9 and 1.2 m) on corn ( Zea mays L.), soybean ( Glycine max L.), sugarbeet ( Beta vulgaris subsp. vulgaris L.) yield and residual soil nitrate‐nitrogen (NO3 –N) contents. Subsurface drain spacing had mixed effects on crop yield. For instance, drain spacing significantly affected corn, soybean, and sugarbeet yield in some, but not all of the 3 yr. The highest corn yield was observed under 9 m spacing and lowest with 15 m spacing for 3‐yr average and 2015 (the wettest year). However, wider spacing (15 m) recorded the highest corn yield during 2017 (the driest year). Similarly, sugarbeet yield was highest with the 15 m subsurface spacing (2017), soybean with 9 m spacing (2015 and 3‐yr average). Drain depth had no effect on corn and soybean yield, except for sugarbeet where the 1.2‐m depth had higher yield. The highest residual soil NO3 –N for corn occurred for the narrower drain spacing (9 m), and 12 m spacing for sugarbeet in 2016. These data indicated that narrow spaced subsurface drains in poorly‐drained, frigid clay soils may increase corn and soybean yield during wet years, but that wider spacing may be beneficial during relatively dry years along 450 km extent of the RRVN.